Ayer dan Kritik Logical-Positivism: Studi Metafisika Ketuhanan - Husna Amin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2015)
Intellect as perception never falls to be perceived mind without losing a large part of its substantial real during the perception. Intellect in itself has potential to evade from any attempt to perceive things objectively. Its ability to comprehensively explain subject is illogical because human’ capacity determines discourses that reveal rejection to it such as science, which is making attempt to deeply penetrate the field of religious and theological discourses. When human could not understand the intellect in them, so how could human understand the higher state than human consciousness in the hierarchy of existence? Being in the highest state, God undeservedly goes down to the realm of human knowledge. In the other words, God understands human, but human could not expect to understand God. At the same time, in the middle of the faith wave, human acknowledge that God is an indefinite mystery and is not reality that human intellect could perceive and understand. This article explores the positivism logic of Alfred Ayer and his critic to metaphysic of God